An Overview of Housing Purchase and Delivery System in Malaysia - Arzwin Binti Mohamed Aris, Nur; Syazli Fathi, Mohamed; Nahar Harun, Aizul; Mohamed, Zainai (International Journal of Engineering and Technology, 2018)
Two types of the housing delivery system (HDS) were used in providing houses in the Malaysia market. However concept and differences between this two systems are not yet discussed in the feature diagram in giving comprehensive understanding the process purchasing a house. Thus, the purpose of this paper is to provide an overview of the process of purchasing a house using two types of HDS which are Sell then Build (STB) system and Build then Sell (BTS) system in Malaysia. This paper first reviews the timeline of HDS and housing provision in Malaysia and later reviews the differences between Sell then Build (STB) system and Build then Sell (BTS) system in the process purchasing a house. The process of purchasing a house in HDS involves a developer, a house buyer, and a financial institution as depicted in the model diagram. The differences of purchasing a house between the two HDS can obviously seen in the financial transaction during the construction stage in which the developer crucially needs fund in completing housing development. This review also highlights the concept, issues, advantages, and disadvantages of both HDS from the perspective of a developer, a house buyer, and the financial institution.Â Â